Accidental and experimental salinomycin poisoning in rabbits - Peixoto,Paulo Vargas (2009)
An outbreak of salinomycin poisoning in rabbits is described. At least 27 out of 2,000 rabbits reared on a farm died after the coccidiostatic drug sulfaquinoxaline was substituted by salinomycin in the feed. An average of 26.9ppm salinomycin was detected in the ration given to the rabbits. Clinical signs included anorexia, apathy and bradykinesia, which progressed to incoordination and recumbency. Gross lesions consisted of pale areas in the skeletal muscles. The histopathological findings showed severe necrotic degenerative myopathy in association with infiltration of neutrophils and macrophages. One rabbit exhibited similar alterations in the myocardium. Mineralization was observed in the affected skeletal muscles in some cases. In order to verify if the poisoning was due to salinomycin, 20 rabbits were divided into five groups and a ration containing the drug at doses of 10, 25, 50, 75 and 100ppm was given. The administration of doses higher than 50ppm resulted in manifestation of the clinical signs seen in the outbreak of poisoning. It was concluded, that probably an error related to the mixture of salinomycin in the feed was the cause of deaths in the spontaneous outbreak of poisoning on the rabbit farm.